2004
DOI: 10.1007/s00198-004-1615-4
|View full text |Cite
|
Sign up to set email alerts
|

Back pain, disability, and radiographic vertebral fracture in European women: a prospective study

Abstract: Vertebral fractures are associated with back pain and disability. There are, however, few prospective data looking at back pain and disability following identification of radiographic vertebral fracture. The aim of this analysis was to determine the impact of radiographically identified vertebral fracture on the subsequent occurrence of back pain and disability. Women aged 50 years and over were recruited from population registers in 18 European centers for participation in the European Prospective Osteoporosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 17 publications
3
48
1
9
Order By: Relevance
“…(16) Another group reported that the presence of T2DM was an independent risk factor for prevalent VFs in Japanese men aged 50 years and older (OR, 4.73; 95% CI, 2.19 to 10.2) after adjusting for age, BMI, and lumbar spine BMD. (20) Because VFs are a major cause of pain and disability, (36,37) it is important to identify subjects at increased risk of VFs. In the present analysis, having diabetes was not statistically significantly associated with increased odds of prevalent or incident VFs.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Another group reported that the presence of T2DM was an independent risk factor for prevalent VFs in Japanese men aged 50 years and older (OR, 4.73; 95% CI, 2.19 to 10.2) after adjusting for age, BMI, and lumbar spine BMD. (20) Because VFs are a major cause of pain and disability, (36,37) it is important to identify subjects at increased risk of VFs. In the present analysis, having diabetes was not statistically significantly associated with increased odds of prevalent or incident VFs.…”
Section: Discussionmentioning
confidence: 99%
“…In case the trabecular bone is substantially affected, compression fractures of the thoracic and lumbar vertebrae are common (Kanesaki 2004); should the cortical bone be affected, fractures of the femoral neck are likely to occur especially in postmenopausal women (Horikoshi et al 1999). Such fractures usually induce acute lumbar or thoracic pain, and vertebral deformities subsequently developing after vertebral fractures cause chronic low back pain (O'Neill et al 2004).…”
mentioning
confidence: 99%
“…Moreover, about 10% of these patients had severe and/or multiple vertebral fractures. These numbers are of clinical relevance, considering the frailty of elderly patients with HF (2) and the prognostic aspects related to vertebral fractures in the general populations (28,29,35,36,37). Indeed, vertebral fractures, even when mild or asymptomatic, are a negative prognostic factor for further vertebral and nonvertebral fractures (35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vertebral fractures, even when mild or asymptomatic, are a negative prognostic factor for further vertebral and nonvertebral fractures (35). Symptomatic vertebral fractures are also a major cause of disability with consequent significant limitations in daily living activities (36).…”
Section: Discussionmentioning
confidence: 99%